Optimization of a Cisplatin Model of Chemotherapy-Induced Peripheral Neuropathy in Mice: Use of Vitamin C and Sodium Bicarbonate Pretreatments to Reduce Nephrotoxicity and Improve Animal Health Status. (4th September 2014) - Guindon, Josée; Deng, Liting; Fan, Baochang; Wager-Miller, Jim; Hohmann, Andrea G
Background: Cisplatin, a platinum-derived chemotherapeutic agent, produces antineoplastic effects coupled with toxic neuropathic pain and impaired general health status. These side-effects complicate long term studies of neuropathy or analgesic interventions in animals. We recently demonstrated that pretreatment with sodium bicarbonate (4% NaHCO3 ) prior to cisplatin (3 mg/kg i.p. weekly up to 5 weeks) was associated with improved health status (i.e. normal weight gain, body temperature, creatinine and ketone levels, and kidney weight ratio) in rats (Neurosci Lett 544:41–46, 2013). To reduce the nephrotoxic effects of cisplatin treatment in mice, we compared effects of sodium bicarbonate (4% NaHCO3 s.c.), vitamin C (25 mg/kg s.c.), resveratrol (25 mg/kg s.c)*** and saline (0.9% NaCl) pretreatment on cisplatin-induced changes in animal health status, neuropathic pain and proinflammatory cytokine levels in spinal cord and kidney. Results: Cisplatin-treated mice receiving saline pretreatment exhibited elevated ketone, creatinine and kidney weight ratios, representative of nephrotoxicity. Vitamin C and sodium bicarbonate lowered creatinine/ketone levels and kidney weight ratio whereas resveratrol normalized creatinine levels and kidney weight ratios similar to saline pretreatment. All pretreatments were associated with decreased ketone levels compared to saline pretreatment. Cisplatin-induced neuropathy (i.e. mechanical and cold allodynia) developed equivalently in all pretreatment groups and was similarly reversed by either morphine (6 mg/kg i.p.) or ibuprofen (6 mg/kg i.p.) treatment. RT-PCR showed that mRNA levels for IL-1β were increased in lumbar spinal cord of cisplatin-treated groups pretreated with either saline, NaHCO3 or resveratrol/cisplatin-treated groups. However, IL-6 and TNF-alpha were elevated in the kidneys in all cisplatin-treated groups. Our studies also demonstrate that 60 days after the last cisplatin treatment, body weight, body temperature, kidney functions and mRNA levels have returned to baseline although the neuropathic pain (mechanical and cold) is maintained. Conclusions: Studies employing cisplatin should include NaHCO3 or vitamin C pretreatment to improve animal health status and reduce nephrotoxicity (lower creatinine and kidney weight ratio) without affecting the development of chemotherapy-induced neuropathy or analgesic efficacy.